2020
DOI: 10.3389/fncel.2020.00233
|View full text |Cite
|
Sign up to set email alerts
|

Immune Factor, TNFα, Disrupts Human Brain Organoid Development Similar to Schizophrenia—Schizophrenia Increases Developmental Vulnerability to TNFα

Abstract: Schizophrenia (SZ) is a neurodevelopmental genetic disorder in which maternal immune activation (MIA) and increased tumor necrosis factor-α (TNF-α) may contribute. Previous studies using iPSC-derived cerebral organoids and neuronal cells demonstrated developmental malformation and transcriptional dysregulations, including TNF receptors and their signaling genes, common to SZ patients with diverse genetic backgrounds. In the present study, we examined the significance of the common TNF receptor dysregulations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 53 publications
(144 reference statements)
3
27
0
Order By: Relevance
“…The rotenone induced depletion of the Ki67 + cell organoids develop distinct structures: Ventricular zone, intermediate zone, cortical zone, and marginal zone reminiscent of the human brain structures developing in the 1 st and early 2 nd trimesters. As previously shown [38,41], most of the Ki67 + cells were located in rosettes in the ventricular zone, where the proliferating stem/progenitor cells reside. Few of the Ki67 + cells migrated to the intermediate and cortical zones.…”
Section: Effects Of Rotenone Treatmentssupporting
confidence: 72%
See 2 more Smart Citations
“…The rotenone induced depletion of the Ki67 + cell organoids develop distinct structures: Ventricular zone, intermediate zone, cortical zone, and marginal zone reminiscent of the human brain structures developing in the 1 st and early 2 nd trimesters. As previously shown [38,41], most of the Ki67 + cells were located in rosettes in the ventricular zone, where the proliferating stem/progenitor cells reside. Few of the Ki67 + cells migrated to the intermediate and cortical zones.…”
Section: Effects Of Rotenone Treatmentssupporting
confidence: 72%
“…Sections were stained in batches consisting all representative sections from each experimental group and control, as described in Benson, et al [41]. The following primary antibodies were used: Anti-Ki67 polyclonal (rabbit) antibody (Cat #: ab15580, abcam) proliferation marker, and mouse monoclonal anti-O4 antibody IgM at dilution 1:330 (Cat #: MO15002.9, Neuromics), oligodendrocyte Marker.…”
Section: Immuncytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“… 89 , 90 Patient-derived organoids confirmed the hypothesized impaired telencephalic neuronal development, attributing it to reduced FGFR1 expression, and also demonstrated aberrant immune response, mitochondrial function, increased TNFα and decreased Wnt signaling, and excitatory/inhibitory neurotransmission. 91 95 …”
Section: Brain Organoid Models For Oud and Neuropsychiatric Diseasesmentioning
confidence: 99%
“…89,90 Patient-derived organoids confirmed the hypothesized impaired telencephalic neuronal development, attributing it to reduced FGFR1 expression, and also demonstrated aberrant immune response, mitochondrial function, increased TNFα and decreased Wnt signaling, and excitatory/inhibitory neurotransmission. [91][92][93][94][95] In addition, mutations in DISC1(disrupted-inschizophrenia 1) have been established as a genetic risk factor for various psychiatric disorders including schizophrenia, but the mechanism of how DISC1 disrupts brain function is not well known. 96,97 Cerebral organoids suggested that disturbing the interaction between DISC1 and Ndel1/Nde1 impairs cell-cycle progression during mitosis.…”
Section: Psychotic Disordersmentioning
confidence: 99%